Implementasi Media Pembelajaran Ludaar Berbasis Team Game Tournament Untuk Mengenalkan Tari Tradisional Indonesia Dalam Pendidikan Pancasila - Muhammad Ilham Cahyo Utomo; Panca Dewi Purwati (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This less than optimal use of media makes students quickly feel bored because they think the learning is monotonous and not varied. That is what affects student learning outcomes that have not been maximized. The purpose of this study is to describe the design of Ludaar media to introduce Indonesian traditional dance and describe the learning steps using team game tournament-based ludaar media. The method used is a qualitative method with a library study model approach. This AR cultural ludo media (Ludaar) is quite innovative media because in it there is the use of contemporary technology such as Augmented Reality (AR). In using this media, students are directly involved and have two-way interaction from teachers and students. Because this AR cultural ludo media (Ludaar) is in the form of a game, the suitable model to be applied with this media is the team game tournament model.